2017
DOI: 10.1096/fj.201601169r
|View full text |Cite
|
Sign up to set email alerts
|

Altered methylation of specific DNA loci in the liver of Bhmt‐null mice results in repression of Iqgap2 and F2rl2 and is associated with development of preneoplastic foci

Abstract: Folate B-dependent remethylation of homocysteine is important, but less is understood about the importance of the alternative betaine-dependent methylation pathway-catalyzed by betaine-homocysteine methyltransferase (BHMT)-for establishing and maintaining adequate DNA methylation across the genome. We studied C57Bl/6J (betaine-homocysteine methyltransferase)-null mice at age 4, 12, 24, and 52 wk ( = 8) and observed elevation of -adenosylhomocysteine concentrations and development of preneoplastic foci in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…One of the important functions of choline is to serve as a methyl-group donor used for the synthesis of Ado-Met (1). AdoMet concentrations are diminished, and S-adenosylhomocysteine (AdoHcy) concentrations are increased in animals consuming LC diets (33,34); the ratio of these 2 metabolites determines the rate of methylation reactions (35,36). Therefore, we assayed AdoMet and AdoHcy concentrations in AC and LC E17 brains.…”
Section: Choline-mediated Changes In Methylation Potential Regulate Ementioning
confidence: 99%
“…One of the important functions of choline is to serve as a methyl-group donor used for the synthesis of Ado-Met (1). AdoMet concentrations are diminished, and S-adenosylhomocysteine (AdoHcy) concentrations are increased in animals consuming LC diets (33,34); the ratio of these 2 metabolites determines the rate of methylation reactions (35,36). Therefore, we assayed AdoMet and AdoHcy concentrations in AC and LC E17 brains.…”
Section: Choline-mediated Changes In Methylation Potential Regulate Ementioning
confidence: 99%
“…While some oncogenes such as c-myc were hypomethylated in this low choline-diet rodent model, the promoter of some tumor suppressor genes such as p53, p16INK4a, PtprO, Cdh1, and Cx26 was hypermethylated [170,171,172]. In support of the role of betaine and choline in protecting against hepatocellular carcinoma, Lupu et al, [173] reported that, in a mouse model, the deletion of betaine-homocysteine methyltransferase gene, which is implicated in choline metabolism resulted in the spontaneous elevation of S-adenosylhomocysteine levels and development of preneoplastic foci in the liver.…”
Section: Micronutrients and Dna Methylation And Their Impact On Camentioning
confidence: 74%
“…The fourth gene in this region, ARSB , plays no apparent role in betaine metabolism, but does impact body size and craniofacial morphology through alternative mechanisms. However, variation in the nearby BHMT gene is associated with differential methylation of ARSB , which can modulate ARSB expression (Lupu et al. 2017).…”
Section: Resultsmentioning
confidence: 99%